Pooh's graduation - Gaines, Isabel; La Paz, Orlando de; Thompson, Dana; Thompson, Del; Milne, A. A. (Alan Alexander), 1882-1956. (New York : Disney Press, 2000)
As Christopher Robin prepares a graduation celebration for his friends in the Hundred-Acre Wood, Winnie the Pooh wonders what his special award might be.
"Based on the Pooh stories by A.A. Milne"--Copr. p.
79129
Keywords: Graduation (School) -- Fiction; Friendship -- Fiction; Teddy bears -- Fiction; Toys -- Fiction; Bears -- Juvenile fiction; Winnie-the-Pooh (Fictitious character)